2009
DOI: 10.1016/j.molcel.2009.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Two Mammalian MOF Complexes Regulate Transcription Activation by Distinct Mechanisms

Abstract: SUMMARY In mammals, MYST family histone acetyltransferase MOF plays important roles in transcription activation by acetylating histone H4 on K16, a prevalent mark associated with chromatin decondensation, and transcription factor p53 on K120, which is important for activation of pro-apoptotic genes. However, little is known about MOF regulation in higher eukaryotes. Here, we report that the acetyltransferase activity of MOF is tightly regulated in two different but evolutionarily conserved complexes, MSL and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
183
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(186 citation statements)
references
References 47 publications
3
183
0
Order By: Relevance
“…So far, hMOF is known to be contained in two different complexes, MOF-MSL and MOF-MSL1v1 [15,34]. Both the complexes have acetyltransferase activity toward nucleosomal H4, but free hMOF barely showed any activity toward HeLa nucleosomes [35,36], even though MOF has been shown to be able to bind to the chromatin [37]. Our results showed that free hMOF acetylates itself in the MYST domain, and autoacetylation greatly decreased its binding to reconstituted nucleosomes or native HeLa nucleosomes.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…So far, hMOF is known to be contained in two different complexes, MOF-MSL and MOF-MSL1v1 [15,34]. Both the complexes have acetyltransferase activity toward nucleosomal H4, but free hMOF barely showed any activity toward HeLa nucleosomes [35,36], even though MOF has been shown to be able to bind to the chromatin [37]. Our results showed that free hMOF acetylates itself in the MYST domain, and autoacetylation greatly decreased its binding to reconstituted nucleosomes or native HeLa nucleosomes.…”
Section: Discussionmentioning
confidence: 68%
“…First, certain deacetylases (for example SIRT1) may remove acetylation of hMOF and increase its interaction with the nucleosomal substrate ( Figure 9). Second, the well-studied proteins in different hMOF complexes, like MSL1/2/3 and MSL1v1 [35,36], may interfere with the autoacetylation of hMOF so as to facilitate targeting of hMOF to specific substrates, or meanwhile, stabilize its interaction with the substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, p90 does not appear to affect growth-arrest targets such as p21. To dissect the molecular mechanism underlying this differential regulation, we found that p90 interacts with the Tip60 acetyltransferase and promotes Tip60-mediated acetylation of p53 at K120, a posttranslational modification that has previously been reported to modulate the decision between cell cycle arrest and apoptosis (15)(16)(17). Thus, p90 likely serves as an upstream regulator of the p53-Tip60 interplay that is required for apoptotic signaling and allows for transcription induction of PUMA in cells at risk of DNA damage.…”
Section: Discussionmentioning
confidence: 95%
“…There is accumulating evidence indicating that acetylation of p53 plays a major role in activating p53 function during stress responses (2,13,14). Following our early findings of C terminus p53 acetylation, we and others recently showed that p53 is also acetylated by Tip60 (also known as KAT5)/MOF (human ortholog of males absent on the first) at residue Lys120 (K120) within the DNA-binding domain (15)(16)(17). K120 acetylation is crucial for p53-mediated apoptosis but has no obvious effect on p21 expression, an essential target of p53-mediated growth arrest.…”
mentioning
confidence: 78%